Efficient modification of PAMAM G1 dendrimer surface with β-cyclodextrin units by CuAAC: impact on the water solubility and cytotoxicity. Issue 43 (7th July 2020) - Sorroza-Martínez, Kendra; González-Méndez, Israel; Martínez-Serrano, Ricardo D.; Solano, José D.; Ruiu, Andrea; Illescas, Javier; Zhu, Xiao Xia; Rivera, Ernesto
Abstract : The toxicity of the poly(amidoamine) dendrimers (PAMAM) caused by the peripheral amino groups has been a limitation for their use as drug carriers in clinical applications. Abstract : The toxicity of the poly(amidoamine) dendrimers (PAMAM) caused by the peripheral amino groups has been a limitation for their use as drug carriers in clinical applications. In this work, we completely modified the periphery of PAMAM dendrimer generation 1 (PAMAM G1) with β-cyclodextrin (β-CD) units through the Cu(i )-catalyzed azide–alkyne cycloaddition (CuAAC) to obtain the PAMAM G1-β-CD dendrimer with high yield. The PAMAM G1-β-CD was characterized by 1 H- and 13 C-NMR and mass spectrometry studies. Moreover, the PAMAM G1-β-CD dendrimer showed remarkably higher water solubility than native β-CD. Finally, we studied the toxicity of PAMAM G1-β-CD dendrimer in four different cell lines, human breast cancer cells (MCF-7 and MDA-MB-231), human cervical adenocarcinoma cancer cells (HeLa) and pig kidney epithelial cells (LLC-PK1). The PAMAM G1-β-CD dendrimer did not present any cytotoxicity in cell lines tested which shows the potentiality of this new class of dendrimers.